Pengaruh Brand Ambassador Dan Celebrity Endorses Terhadap Loyalitas Pelanggan Pada Produk Ms. Glow (Studi Kasus Pada Pengguna Yang Mengikuti Akun Ms. Glow Official Pada Aplikasi Instagram) - Aldi Aldiyansyah Sopandi; Acep Samsudin (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Based on the We Are Social and Hootsuite Digital Report Survey (2022), at the beginning of 2022, there will be 4.95 billion people worldwide using the internet, or 62.5% of the world's population. the Instagram application occupies the 4th position as a user of the social platform. Customer loyalty is a form of a consumer's preference for a brand when compared to other brands. In this study aims to determine the effect of Brand Ambassadors and Celebrity Endorses on customer loyalty.This research was conducted on all MS Glow users. This study uses primary data with questionnaire data collection techniques. The method in this study uses quantitative methods. Test analysis was carried out using Validity, Reliability, classical assumptions, hypothesis testing and data analysis using SPSS 25. The results of the data analysis test showed that brand ambassadors and celebrity endorsers simultaneously had an impact on customer loyalty. Partially brand ambassadors and celebrity endorses have an impact on customer loyalty. The conclusion from this study is that the independent variables, namely brand ambassadors and celebrity endorsers, partially influence and affect the dependent variable, namely customer loyalty.